2002
DOI: 10.1067/mcp.2002.129068
|View full text |Cite
|
Sign up to set email alerts
|

Application of semisimultaneous midazolam administration for hepatic and intestinal cytochrome P450 3A phenotyping

Abstract: Midazolam pharmacokinetic parameters that are specific to liver and intestinal metabolism were not different between the traditional and semisimultaneous methods. The semisimultaneous method also yielded expected marked changes in the parameters as a result of ketoconazole inhibition. Thus the semisimultaneous midazolam method appears to be a suitable approach to determine hepatic and intestinal CYP3A activity at baseline and with enzyme inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
64
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 27 publications
10
64
2
Order By: Relevance
“…Our results showed that two weeks ingestion of tenryocha and rooibos tea caused significant declines in AUC and C max of MDZ while there was no change in the elimination half life (Table 1). MDZ is a short-acting benzodiazepine derivative that is metabolized to 1'-hydroxymidazolam and 4-hydroxymidazolam mainly by CYP3A4 in humans and by CYP3A2 in rats, and it has been recognized as a sensitive prove to investigate CYP3A function (30,31). CYP3A enzyme is known to be expressed mainly in the liver and intestine, and both of them play important roles in drug metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that two weeks ingestion of tenryocha and rooibos tea caused significant declines in AUC and C max of MDZ while there was no change in the elimination half life (Table 1). MDZ is a short-acting benzodiazepine derivative that is metabolized to 1'-hydroxymidazolam and 4-hydroxymidazolam mainly by CYP3A4 in humans and by CYP3A2 in rats, and it has been recognized as a sensitive prove to investigate CYP3A function (30,31). CYP3A enzyme is known to be expressed mainly in the liver and intestine, and both of them play important roles in drug metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic (ERH = CLiv/QH) and gastrointestinal extraction ratio (ERG = 1 − F/1 − ERH) were calculated assuming a liver blood flow (QH) of 25.4 ml min −1 × body weight (kg) × (1 − haematocrit) [16]. Bioavailability was calculated as follows:…”
Section: Pharmacokinetic Analysis and Statistical Evaluationmentioning
confidence: 99%
“…A complete search of the literature using the Metabolism and Transport Drug Interaction Database (University of Washington, Seattle, WA) indentified 11 clinical DDI studies and 16 dosage scenarios from 17 published clinical results using midazolam as CYP3A probe (intravenous and oral) and ketoconazole as inhibitor (400 mg QD and 200 mg QD and BID for various durations) as of 2012 (Olkkola et al, 1994;McCrea et al, 1999;Tsunoda et al, 1999;Goh et al, 2002;Lee et al, 2002;Lam et al, 2003;Eap et al, 2004;Chung et al, 2006;Tham et al, 2006;Yong et al, 2008;Krishna et al, 2009;Stoch et al, 2009). The specific treatment regimens of ketoconazole and midazolam used in the literature reports were reproduced in the simulations.…”
Section: Model Validation and Simulationmentioning
confidence: 99%